TRANSFORMATIVE IMPACT OF ISLAMIC THERAPY METHODS ON BEHAVIOR AND WORSHIP AWARENESS OF DRUG PATIENTS IN SEIKAMBING NARCOTICS REHABILITATION - Syavika, Nurul; Muktarruddin, Muktarruddin (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
This research aims to examine the impact of Islamic Therapy Method on the behavior and worship awareness of drug patients in the Seikambing Narcotics rehabilitation center. The study employs a descriptive qualitative research design. Data collection involved observations and interviews, while data analysis included data reduction, presentation, and drawing conclusions. The validity of the data was ensured through source triangulation. The findings indicate significant changes in the behavior and worship awareness of drug patients as a result of the implementation of Islamic therapy methods. Aggressive behavior transformed into polite and gentle behavior, and high emotional behavior became more manageable. Additionally, patients exhibited improved dedication to worship, as they continued to engage in religious practices and demonstrated consistency in their commitment.